Where the millennials will take us a new generation wrestles with the gender structure - Barbara J. Risman (New York : Oxford University Press, 2018)
"Are today's young adults gender rebels or returning to tradition? In Where the Millennials Will Take Us, Barbara J. Risman reveals the diverse strategies youth use to negotiate the ongoing gender revolution. Risman offers a revision of her theory of gender as a social structure and uses it to analyze life history interviews with a diverse set of Millennials to probe their gender identities, what they believe others expect of them, their ideologies, and their hopes and dreams for the future."-- Page 4 of cover
Keywords: Gender expression; SOCIAL SCIENCE Sociology Social Theory